2013
DOI: 10.2174/1874192401307010054
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cognitive Function, Depression/Anxiety and Functional Parameters in Patients Admitted for Congestive Heart Failure

Abstract: Cognitive impairment, anxiety and depression have been described in patients with congestive heart failure (CHF). We analyzed in-hospital CHF patients before discharge with neuropsychological tests attempting to correlate with prognostic parameters.Methods: All subjects underwent a mini mental state examination (MMSE), geriatric depression scale (GDS), anxiety and depression scale test (HADS). We evaluated NYHA class, brain natriuretic peptide (BNP), left ventricular ejection fraction (LVEF) and non-invasive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
(37 reference statements)
2
32
0
2
Order By: Relevance
“…Other studies reporting feasibility of exercise in AHF have excluded patients with non-HF conditions affecting mobility(1214) and generally enrolled younger patients with less severe renal dysfunction(13, 14). A study without exclusion for limited mobility and with a mean age similar to RED-ROSE, reported that 69% of patients could perform a walk test at discharge,(15) similar to our findings where 70% of eligible patients could perform the step test at 72 hours after enrollment. Thus, while exercise provocation did induce more severe dyspnea in 29% of patients, feasibility was too low to allow incorporation into a clinical trial endpoint.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies reporting feasibility of exercise in AHF have excluded patients with non-HF conditions affecting mobility(1214) and generally enrolled younger patients with less severe renal dysfunction(13, 14). A study without exclusion for limited mobility and with a mean age similar to RED-ROSE, reported that 69% of patients could perform a walk test at discharge,(15) similar to our findings where 70% of eligible patients could perform the step test at 72 hours after enrollment. Thus, while exercise provocation did induce more severe dyspnea in 29% of patients, feasibility was too low to allow incorporation into a clinical trial endpoint.…”
Section: Discussionsupporting
confidence: 89%
“…Scores ranging from 27 to 30 are considered normal in the general population; scores between 21 and 26 reflect mild cognitive impairment; scores between 10 and 19 are considered moderate impairment; a score below 10 is considered severe impairment (Tombaugh and McIntyre, 1992). The MMSE has been used extensively in heart failure patients (Caminiti et al, 2012;Feola et al, 2013). Cronbach's alpha of the MMSE was 0.83 in this study.…”
Section: Instrumentsmentioning
confidence: 79%
“…Recently, Feola et al analyzed the connection between MDD, cognitive impairment and specific objective parameters characterizing heart failure (BNP, ejection fraction, cardiac output, etc.) in a group of 303 patients hospitalized for congestive heart failure [24]. Other authors debated the influence of MDD on the occurrence and evolution of heart failure.…”
Section: Discussionmentioning
confidence: 99%